2021
DOI: 10.4236/ojapps.2021.116054
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Levels of Flavonols Myricetin, Quercetin and Kaempferol—In Kenyan Tea (<i>Camellia sinensis L.</i>) with Processed Tea Types and Geographic Location

Abstract: The aim of this study was to determine the levels of myricetin, quercetin, and kaempferol in green and black Kenyan types in relation to geographic location of production. Tea samples were extracted before chromatographic separations with a Shimadzu 20A HPLC coupled with PDA. Flavonol levels were quercetin > kaempferol > myricetin. Teas from east of rift, had quercetin 1.25 -1.83 mg/g and 1.29 -1.71 mg/g for green and black types, respectively. Kaempferol levels were between 1.28 -1.72 mg/g in green and 1.36 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Catechin and epicatechin are flavanols that are often found in fruits, vegetables, and tea [ 36 ]. Quercetin and kaempferol are flavonols that are particularly present in black and green tea, as well as fruits such as pomegranate and banana [ 37 , 38 ]. Both flavanols and flavonols have an antioxidant capacity associated with flavonoids, which causes a high redox potential, and therefore, a high reducing capacity (antioxidant action).…”
Section: Resultsmentioning
confidence: 99%
“…Catechin and epicatechin are flavanols that are often found in fruits, vegetables, and tea [ 36 ]. Quercetin and kaempferol are flavonols that are particularly present in black and green tea, as well as fruits such as pomegranate and banana [ 37 , 38 ]. Both flavanols and flavonols have an antioxidant capacity associated with flavonoids, which causes a high redox potential, and therefore, a high reducing capacity (antioxidant action).…”
Section: Resultsmentioning
confidence: 99%
“…Through PPI analysis, we know that the main targets are quercetin and kaempferol, the two most common avonol glycosides. Previous studies have shown that quercetin and kaempferol play a signi cant role in anti-in ammation, anti-tumor and reducing blood lipids [20][21]. Therefore, we chose these two monomers to verify the positive effect of Kudingcha on obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Through PPI analysis, we know that the main targets are quercetin and kaempferol, the two most common avonol glycosides. Previous studies have shown that quercetin and kaempferol play a signi cant role in anti-in ammation, anti-tumor and reducing blood lipids (Kingori et al 2021;Gaikwad 2018). Therefore, we chose these two monomers to verify the positive effect of Kudingcha on obesity.…”
Section: The Mechanism Of Quercetin and Kaempferol Treated With Obesitymentioning
confidence: 99%